HOLOCENE ECOLOGICAL TRAJECTORIES IN LAKE AND WETLAND SYSTEMS (AUVERGNE, FRANCE): A PALAEOENVIRONMENTAL CONTRIBUTION FOR A BETTER ASSESSMENT OF ECOSYSTEM AND LAND USE ‘S VIABILITY IN MANAGEMENT STRATEGIES. - Miras, Y.; Lavrieux, M.; Florez, M. (Annali di Botanica, 2013)
Multi-proxy palaeoenvironmental studies are very important for the development of sustainable management strategies for ecosystems and modern landscapes. Analysing the relationship between societies, climate and environments through time, these studies contribute to define adequate policies and strategies for socio-environmental management, protection and legacy. Two complementary case studies– Aydat lake and Espinasse fen - from the south of the Chaîne des Puys (Auvergne, Massif Central, France) are presented. The analysis of these sedimentological records (both lacustrine and peat) follows a multi-proxy approach combining abiotic and biotic palaeoindicators (density, magnetic susceptibility, X-Ray Fluorescence spectrometry, Rock-Eval, pollen, non-pollen palynomorphs, molecular biomarkers). Aydat lake and Espinasse fen analyses were performed following a high spatio-temporal resolution. Results underline that long-term models of detrital input and eutrophication correspond to complex patterns with early and recurrent phases of human-induced ecological disturbances. They also evidence the existence of diversified long-term land use systems (deforestation, grazing, agriculture, hemp culture and retting) that provide fresh insights into the understanding of present-day mountain environments. This history between diversified human activities and hydrosystems responses must be taken into account for the construction of accurate retrospective and prospective model simulations of hydrosystem functioning.